Implementation of Balanced Scorecard and Financial Performance of SMEs - Hamza Zaheer; Adnan Ramzan; Kashif Mahmood; Muhammad Noman Nagra (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
In a very dynamic business environment of today, it is a big challenge for small and medium enterprises (SMEs) particularly working in developing countries to unremittingly adapt swift techno-ecological developments and improve their performance on broad frontiers. The balanced scorecard (BSC) is widely propagated as one of the strategic policy instruments for achieving the desired level of performance by aligning the performance measurement systems with the strategic objectives. This study is aimed to examine the effect of BSC implementation as a strategic instrument of performance measure on the financial performance of SMEs. For the said purpose, this study used four facets of BSC i.e., financial perspective, customer perspective, internal processes and learning growth perspective are used as independent variables. A questionnaire adopted from previous studies based upon resource-based view and balance card theory was used to gather the data from SMEs. For data collection, 400 questionnaires containing closed ended questions were sent to chief financial officers and chief operating officers of SMEs located in Lahore district. Only three hundred and eighty (380) respondents returned duly filled questionnaires. Out of which 72 are from service sector and the remaining 308 were from industrial sector. The findings of the study revealed that implementation of balanced scorecard has significant positive impact on the financial performance of SMEs. All four facets of BSC are found positively related with the financial performance. The study is helpful for SMEs to use BSC to get better performance. However, the successful implementation of BSC requires commitment and allocation of adequate resources. There is a need to explore the challenges and barriers confronted in the successful implementation BSC.